BCR-Induced Ca2+ Signals Dynamically Tune Survival, Metabolic Reprogramming, and Proliferation of Naive B Cells - Berry, Corbett T.; Liu, Xiaohong; Myles, Arpita; Nandi, Satabdi; Chen, Youhai H.; Hershberg, Uri; Brodsky, Igor E.; Cancro, Michael P.; Lengner, Christopher J.; May, Michael J.; Freedman, Bruce D. (Cell reports (Cambridge), 2020)
B cell receptor (BCR) engagement induces naive B cells to differentiate and perform critical immune-regulatory functions. Acquisition of functional specificity requires that a cell survive, enter the cell cycle, and proliferate. We establish that quantitatively distinct Ca2+ signals triggered by variations in the extent of BCR engagement dynamically regulate these transitions by controlling nuclear factor κB (NF-κB), NFAT, and mTORC1 activity. Weak BCR engagement induces apoptosis by failing to activate NF-κB-driven anti-apoptotic gene expression. Stronger signals that trigger more robust Ca2+ signals promote NF-κB-dependent survival and NFAT-, mTORC1-, and c-Myc-dependent cell-cycle entry and proliferation. Finally, we establish that CD40 or TLR9 costimulation circumvents these Ca2+-regulated checkpoints of B cell activation and proliferation. As altered BCR signaling is linked to autoimmunity and B cell malignancies, these results have important implications for understanding the pathogenesis of aberrant B cell activation and differentiation and therapeutic approaches to target these responses. [Display omitted] •BCR signal strength is encoded as quantitatively distinct intracellular Ca2+ signals•Ca2+ dynamics are decoded by NF-κB, NFAT, and mTORC1 to drive cell fates•BCR-induced Ca2+ signals are required for maximal B cell survival and proliferation•CD40 compensates for weak BCR/Ca2+ signals to rescue NF-κB- and mTORC1-dependent fates Berry et al. establish that variations in the strength of BCR engagement are encoded as quantitatively distinct calcium signals that tune B cell fates by dynamically regulating NF-κB, NFAT, and mTORC1 activity. Targeting calcium signaling may thereby serve as an effective treatment strategy for regulating normal and pathological B cell activation.